Strategy of Squid Fisheries Development in Cilacap Ocean Fishing Port - Axeline Estherina Simanjuntak; Mohammad Imron; Mulyono S Baskoro (Departemen PSP IPB, 2019)
Cilacap Ocean Fishing Port (PPS) was a port that is known to have abundant fish resource potential. The catch of squid in Cilacap PPS is a type of squid that is not yet suitable for export because the handling of squid is still needs improvement for the size and shape. The purpose of this study was to calculate the profits of the squid fishery business, analyze the squid fishing season, and develop a squid fisheries development strategy in Cilacap Ocean Fishing Port. The analytical method used is financial analysis, catch season index, and SWOT method. Data collection by taking respondents was done by purposive sampling to get data related to internal factors (strengths and weaknesses) and external factors (opportunities and threats). The results showed that the profits obtained by squid fishermen in the Cilacap Ocean Fishery Port for a year amounted to Rp2,330,520,000.00 with an R / C ratio of 1.27 so the squid fishing business was profitable. The highest squid catching season was in July to August and January to February. Strategies for developing squid fisheries include regulating squid fishing, improving appropriate technology for fishing and management, increasing squid fishing vessels, increasing fishing units, optimizing squid fisheries can be exported, optimizing market demand, socializing to fishermen to help increase fishermen's knowledge of development activities sustainable fisheries, improve management to be more useful. Key words: Cilacap Ocean Fishing Port, development strategy, squid, squid fisheries, squid fishery business